Analysis Of The Lunar Cycle Effect: New Moon And Full Moon On The Price Pattern Of The Sri Kehati Index Over 5 Years (2019-2023) - Muhammad Al Baihaqi; Maheni Ika Sari; Achmad Hasan Hafidzi (Pondok pesantren As-salafiyah As-Safi'iyyah, 2026)
This study investigates the effect of the lunar cycle specifically the new moon and full moon phases on stock price patterns within the SRI KEHATI Index over a five-year period (2019–2023). Financial astrology, which integrates finance, astronomy, and behavioral psychology, has long been debated for its potential influence on investor sentiment and market movements. Using a quantitative research approach, this study analyzes secondary data from 11 companies selected through purposive sampling, resulting in 8,046 total observations across lunar cycles. Abnormal returns were calculated using the market model, and differences in stock price behavior were examined through paired sample t-tests comparing three days before and three days after both the new moon and full moon events. The empirical findings show no significant difference in abnormal returns surrounding either lunar event. Specifically, price patterns before and after the new moon exhibit no observable changes, indicating trend continuity rather than reversal. Likewise, the full moon phase does not produce statistically significant price deviations, suggesting that investor behavior in the SRI KEHATI Index is not influenced by lunar phenomena. These results contrast with prior studies that reported mixed evidence regarding lunar effects on market performance, implying that the impact of astronomical cycles may be context-dependent and vary across indices, time periods, and investor characteristics. Overall, this study concludes that lunar cycles do not affect price patterns in the SRI KEHATI Index. The findings contribute to behavioral finance research by emphasizing the limited role of lunar-driven sentiment in Indonesian sustainable stock indices.